Information systems freshmen teaching: case experience from day one. (2015) - Pflanzl, Nicolas; Bergener, Katrin; Stein, Armin; Vossen, Gottfried
Teaching information systems has been an international challenge for many years now, due to a number of reasons: changing technology, increasing number of applications, addition and modification of pertinent methodologies, to name just a few. Beyond this, the interest from students has been moving up and down over the years, with a recent new high caused by many Gen Y students. This report derives from 20+ years of experience in teaching information systems and summarises our findings as well as our current approach. The latter is characterised by two fundamental decisions: to provide novices with hands-on experience in dealing with information system concepts from day one, and to deliver a reality check on whether someone has chosen the right study subject and, if so, what to expect in study terms and courses to come.